Exosomal miRNAs as potential biomarkers for insulin resistance and metabolic dysfunction-associated steatotic liver disease in children with obesity - Noh, Eu-Seon; Yeum, Yoonseo; Jin, Hye Young; Ryu, Seongho; Hwang, Il Tae (Frontiers in Endocrinology, 2025)
BackgroundMicroRNAs (miRNAs) have emerged as potential biomarkers for insulin resistance-related conditions such as obesity, metabolic syndrome, and metabolic dysfunction-associated steatotic liver disease (MASLD) in adults. However, data in pediatric populations remain limited. This study aimed to compare serum exosomal miRNA expression among children with both obesity and MASLD, children with obesity without MASLD, and healthy controls, and to evaluate associations with insulin resistance markers.MethodsThirty prepubertal children (5 males and 5 females per group) were enrolled: children with both obesity and MASLD (n=10), children with obesity without MASLD (n=10), and healthy controls (n=10). Serum exosomal miRNAs were analyzed using next-generation sequencing. Differential expression analyses were performed between groups, and correlations with clinical and metabolic parameters were assessed, including the triglyceride-glucose (TyG) index, TyG index adjusted for ALT (TyG-ALT), and the homeostatic model assessment for insulin resistance (HOMA-IR).ResultsAll participants were prepubertal, with no significant differences in mean age across groups. miR-34a-5p, miR-122-5p, miR-885-5p, and miR-885-3p were significantly upregulated in children with both obesity and MASLD compared to both other groups, and positively correlated with AST and uric acid levels. Additionally, miR-122-5p, miR-885-5p, and miR-885-3p were associated with ALT and TyG-ALT index. Conversely, miR-570-3p and miR-32-3p were significantly downregulated in children with both obesity and MASLD and negatively correlated with AST, ALT, and TyG-ALT levels.ConclusionsSix exosomal miRNAs (miR-34a-5p, miR-122-5p, miR-885-5p, miR-885-3p, miR-570-3p, and miR-32-3p) were differentially expressed in children with both obesity and MASLD and showed strong correlations with markers of liver function and insulin resistance. These findings suggest their potential as non-invasive biomarkers for early identification of MASLD and related metabolic disturbances in pediatric populations.